Optimised Adaptive Controller for an Interacting System - Preethi, S.; Sanjeevi Gandhi, A. (Asian Journal of Electrical Sciences, 2013)
In this paper, a method for controlling multivariable process is presented. The system under investigation is a two tank interacting process. A decoupler is designed in order to minimize the interaction effects. Then, the Model Reference Adaptive Controller is designed for the process with decoupler block. The tuning parameter is optimised using Genetic Algorithm. Optimised Model Reference Adaptive Controller was then compared with conventional controllers. The performance comparisons have been made in terms of rise time, settling time and performance criteria.